HLA Class II Alleles DRB1*11:01 and DQB1*03:01 Unmask Immunogenetic Susceptibility to Anti-Nivolumab Antibodies in Combination with Ipilimumab - Surendran Rajendran; Andres H. Gutierrez; Ming-Shan Chien; Tracy Tang; Jochem Gokemeijer; Daron Forman; Anne S. De Groot; Vibha Jawa; Lora Hamuro (The AAPS Journal, 2026)

Sex differences in the association between skeletal muscle energetics and perceived physical fatigability: the Study of Muscle, Mobility and Aging (SOMMA) - Emma L. Gay; Paul M. Coen; Stephanie Harrison; Reagan E. Garcia; Yujia Qiao; Bret H. Goodpaster; Daniel E. Forman; Frederico G. S. Toledo; Giovanna Distefano; Philip A. Kramer; Sofhia V. Ramos; Anthony J. A. Molina; et al. (GeroScience, 2024)

Red and processed meat intakes and cardiovascular disease and type 2 diabetes mellitus: An umbrella systematic review and assessment of causal relations using Bradford Hill’s criteria - Erica R. Hill; Lauren E. O’Connor; Yu Wang; Caroline M. Clark; Bethany S. McGowan; Michele R. Forman; Wayne W. Campbell (Critical Reviews in Food Science and Nutrition, 2024)

Chronology and evolution of the world's largest sand island: K'gari (Fraser Island), South East Queensland, Australia - J. Shulmeister; T.M. Rittenour; N.R. Patton; D. Ellerton; A. Gontz; P.A. Hesp; T. Santini; G. Miot da Silva; S. Forman; H. Bowyer; J.T. Kelly; A. McCallum; et al. (Quaternary Science Reviews, 2024)

Lower muscle mitochondrial energetics is associated with greater phenotypic frailty in older women and men: the Study of Muscle, Mobility and Aging - Theresa Mau; Haley N. Barnes; Terri L. Blackwell; Philip A. Kramer; Scott R. Bauer; David J. Marcinek; Sofhia V. Ramos; Daniel E. Forman; Frederico G. S. Toledo; Russell T. Hepple; Stephen B. Kritchevsky; Steven R. Cummings; et al. (GeroScience, 2023)

Active thrust tectonics along the western slope of the Central Andes southernmost Pampean flat-slab segment (∼33°S, Chile): The Cariño Botado fault system - J. Estay; L. Pinto; G. Easton; G.P. De Pascale; M. Troncoso; S. Carretier; S.L. Forman (Geomorphology, 2023)

Ruminative reflection is associated with anticorrelations between the orbitofrontal cortex and the default mode network in depression: implications for repetitive transcranial magnetic stimulation - Tobin J. Ehrlich; Jyoti Bhat; Andrea M. Horwege; Daniel H. Mathalon; Gary H. Glover; Brian J. Roach; Bashar W. Badran; Steven D. Forman; Mark S. George; J. Cobb Scott; Michael E. Thase; Jerome A. Yesavage; et al. (Brain Imaging and Behavior, 2022)
Patients with depression who ruminate repeatedly focus on depressive thoughts; however, there are two cognitive subtypes of rumination, reflection and brooding, each associated with different prognoses. Reflection involves problem-solving and is associated with positive outcomes, whereas brooding involves passive, negative, comparison with other people and is associated with poor outcomes. Rumination has also been related to atypical functional hyperconnectivity between the default mode network and subgenual prefrontal cortex. Repetitive pulse transcranial magnetic stimulation of the prefrontal cortex has been shown to alter functional connectivity, suggesting that the abnormal connectivity associated with rumination could potentially be altered. This study examined potential repetitive pulse transcranial magnetic stimulation prefrontal cortical targets that could modulate one or both of these rumination subtypes. Forty-three patients who took part in a trial of repetitive pulse transcranial magnetic stimulation completed the Rumination Response Scale questionnaire and resting-state functional magnetic resonance imaging. Seed to voxel functional connectivity analyses identified an anticorrelation between the left lateral orbitofrontal cortex (−44, 26, −8; k = 172) with the default mode network-subgenual region in relation to higher levels of reflection. Parallel analyses were not significant for brooding or the RRS total score. These findings extend previous studies of rumination and identify a potential mechanistic model for symptom-based neuromodulation of rumination.

The Oxygen Paradox, the French Paradox, and age-related diseases - Joanna M. S. Davies; Josiane Cillard; Bertrand Friguet; Enrique Cadenas; Jean Cadet; Rachael Cayce; Andrew Fishmann; David Liao; Anne-Laure Bulteau; Frédéric Derbré; Amélie Rébillard; Steven Burstein; et al. (GeroScience, 2017)

Patient and genetic counselor perceptions of in-person versus telephone genetic counseling for hereditary breast/ovarian cancer - Aryana S. Jacobs; Marc D. Schwartz; Heiddis Valdimarsdottir; Rachel H. Nusbaum; Gillian W. Hooker; Tiffani A. DeMarco; Jessica E. Heinzmann; Wendy McKinnon; Shelley R. McCormick; Claire Davis; Andrea D. Forman; Alexandra Perez Lebensohn; et al. (Familial Cancer, 2016)

Diets of deepwater oreos (Oreosomatidae) and orange roughy Hoplostethus atlanticus - J. S. Forman; P. L. Horn; D. W. Stevens (Journal of Fish Biology, 2016)
The diets of black oreo Allocyttus niger , smooth oreo Pseudocyttus maculatus , spiky oreo Neocyttus rhomboidalis and orange roughy Hoplostethus atlanticus were determined from examination of contents of 240, 311, 76 and 415 non‐empty stomachs, from fishes sampled by bottom trawl on Chatham Rise to the east of South Island, New Zealand. Hoplostethus atlanticus had an opportunistic predatory strategy with a broad diet dominated by prawns and mesopelagic teleosts, but with substantial components of mysids and cephalopods. Pseudocyttus maculatus was strongly specialized on gelatinous zooplankton (jellyfish and salps). Allocyttus niger consumed mainly salps and hyperiid amphipods, and to a lesser extent fishes, prawns, mysids and copepods. Neocyttus rhomboidalis primarily consumed salps, along with mysids, euphausiids and fishes. Only P. maculatus did not exhibit significant ontogenetic variation in diet. The diets were also influenced by year and bottom depth. Differences in the distributions and diets of the four species probably reduce conflicts in resource use.

Last interglacial vegetation and climate history from the Portuguese coast - T. A. MINCKLEY; J. A. HAWS; M. M. BENEDETTI; S. C. BREWER; S. L. FORMAN (Journal of Quaternary Science, 2015)
We examine the Atlantic maritime vegetation history from Praia Rei Cortiço, Portugal, to understand natural vegetation patterns and infer climatic conditions during the transition from the last interglacial to early glacial periods. Optically stimulated luminescence dating of quartz grains from sediments surrounding the 1.3‐m‐thick organic deposit date the section to within 120–89 ka. Pollen data were used to reconstruct the vegetation history and determine a range of possible past climates using an ensemble of seven modern analogue approaches. A five‐part environmental sequence transitioned from heath‐pine‐dominated communities, deciduous hardwood forests and pine forests to heathlands surrounded by steppe‐like environments. Mixed temperate and Mediterranean forest elements existed during the last interglacial period at Praia Rei Cortiço, suggesting a proximal limit to these floras. Abundant Fagus pollen (>6%) suggests local beech populations existed within maritime forests of the Iberian Atlantic margin, representing a greater distribution of this genus during interglacial periods than has previously been recognized. Climate reconstructions indicate that variations in moisture availability may have been a major driver of the observed environmental changes.

Connecting Satellite Observations with Water Cycle Variables Through Land Data Assimilation: Examples Using the NASA GEOS-5 LDAS - Rolf H. Reichle; Gabriëlle J. M. De Lannoy; Barton A. Forman; Clara S. Draper; Qing Liu (Surveys in Geophysics, 2014)

Exploring frontal asymmetry using functional near-infrared spectroscopy: a preliminary study of the effects of social anxiety during interaction and performance tasks - Lori-Ann Tuscan; James D. Herbert; Evan M. Forman; Adrienne S. Juarascio; Meltem Izzetoglu; Maria Schultheis (Brain Imaging and Behavior, 2013)

Moon phase influences the diet of southern Ray's bream Brama australis - P. L. Horn; J. S. Forman; M. R. Dunn (Journal of Fish Biology, 2013)
Diet composition of the southern Ray's bream Brama australis was examined from stomach contents of 399 specimens sampled by bottom trawl on Chatham Rise to the east of South Island, New Zealand, over 3 years. Prey items were predominantly mesopelagic fishes and crustaceans. Multivariate analysis indicated that moon phase explained more of the diet variability than any other predictor examined. It appears likely that diet composition is influenced by a combination of changes in both tidal flows and illumination. Different combinations of prey were consumed by B. australis at different times of the lunar cycle. An influence of moon phase on feeding by fishes has rarely been reported, but it is likely that moon phase influences the diets of other species that specialize in mesopelagic prey. The most important prey group by mass for B. australis was Myctophidae (primarily Lampanyctodes hectoris ), followed by Stomiiformes (primarily Maurolicus australis ) and shrimps ( Sergestes spp). An ontogenetic shift in diet was observed, from numerical dominance by small crustaceans including amphipods and euphausiids (with some fishes) in smaller (mass B. australis to pelagic teleost prey (with a few larger crustaceans) in larger (>1440 g) B. australis .

Diet and trophic niche of Antarctic silverfish Pleuragramma antarcticum in the Ross Sea, Antarctica - M. H. Pinkerton; J. Forman; S. J. Bury; J. Brown; P. Horn; R. L. O'Driscoll (Journal of Fish Biology, 2013)
The diet of Antarctic silverfish Pleuragramma antarcticum was evaluated by examining stomach contents of specimens collected in the Ross Sea (71°–77° S; 165°–180° E) in January to March 2008. Pleuragramma antarcticum (50–236 mm standard length, L S ) and prey items were analysed for stable‐isotopic composition of carbon and nitrogen. According to index of relative importance ( I RI ), which incorporates frequency of occurrence, mass and number of prey items, the most important prey items were copepods (81% I RI over all specimens), predominantly Metridia gerlachei and Paraeuchaeta sp., with krill and fishes having low I RI (2·2 and 5·6% I RI overall). According to mass of prey ( M ) in stomachs, however, fishes ( P. antarcticum and myctophids) and krill dominated overall diet (48 and 22% M , respectively), with copepods being a relatively minor constituent of overall diet by mass (9·9% M ). Piscivory by P. antarcticum occurred mainly in the extreme south‐west of the region and near the continental slope. Krill identified to species level in P. antarcticum stomachs were predominantly Euphausia superba (14·1% M ) with some Euphausia crystallophorias (4·8% M ). Both DistLM modelling (PRIMER‐permanova+) on stomach contents (by I RI ) and stepwise generalized linear modelling on stable isotopes showed that L S and location were significant predictors of P. antarcticum diet. Postlarval P. antarcticum (50–89 mm L S ) consumed exclusively copepods. Juvenile P. antarcticum (90–151 mm L S ) consumed predominantly krill and copepods by mass (46 and 30% M , respectively). Small adult P. antarcticum (152–178 mm L S ) consumed krill, fishes and copepods (37, 36 and 15% M , respectively). Large adult P. antarcticum (179–236 mm L S ) consumed predominantly fishes and krill (55 and 17% M , respectively), especially in the north (near the Ross Sea slope) and in the SW Ross Sea. Amphipods were occasionally important prey items for P. antarcticum (western Ross Sea, 39% M ). General concordance between stomach contents and trophic level of P. antarcticum and prey based on δ 15 N was demonstrated. Pleuragramma antarcticum trophic level was estimated as 3·7 (postlarval fish) and 4·1 (fish aged 3+ years).

Dietary partitioning by two sympatric fish species, red cod ( Pseudophycis bachus ) and sea perch ( Helicolenus percoides ), on Chatham Rise, New Zealand - Peter L. Horn; Jeff S. Forman; Matthew R. Dunn (Marine Biology Research, 2012)

Diet and scavenging habits of the smooth skate Dipturus innominatus - J. S. Forman; M. R. Dunn (Journal of Fish Biology, 2012)
The diet of smooth skate Dipturus innominatus was determined from examination of stomach contents of 321 specimens of 29·3–152·0 cm pelvic length, sampled from research and commercial trawlers at depths of 231–789 m on Chatham Rise, New Zealand. The diet was dominated by the benthic decapods Metanephrops challengeri and Munida gracilis , the natant decapod Campylonotus rathbunae and fishes from 17 families, of which hoki Macruronus novaezelandiae , sea perch Helicolenus barathri , various Macrouridae and a variety of discarded fishes were the most important. Multivariate analyses indicated the best predictors of diet variability were D. innominatus length and a spatial model. The diet of small D. innominatus was predominantly small crustaceans, with larger crustaceans, fishes and then scavenged discarded fishes increasing in importance as D. innominatus got larger. Scavenged discards were obvious as fish heads or tails only, or skeletal remains after filleting, often from pelagic species. Demersal fish prey were most frequent on the south and west Chatham Rise, in areas where commercial fishing was most active. Dipturus innominatus are highly vulnerable to overfishing, but discarding practices by commercial fishing vessels may provide a positive feedback to populations through improved scavenging opportunities.

Diet of coastal foraging Eurasian otters (Lutra lutra L.) in Pembrokeshire south-west Wales - Gareth S. Parry; Sue Burton; Bethan Cox; Dan W. Forman (European Journal of Wildlife Research, 2011)

The cag PAI is intact and functional but HP0521 varies significantly in Helicobacter pylori isolates from Malaysia and Singapore - H.-M. A. Schmidt; S. Andres; C. Nilsson; Z. Kovach; N. O. Kaakoush; L. Engstrand; K.-L. Goh; K. M. Fock; D. Forman; H. Mitchell (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

A novel technique for isolating functional mast cells from the heart - L. G. Morgan; S. P. Levick; T. G. Voloshenyuk; D. B. Murray; M. F. Forman; G. L. Brower; J. S. Janicki (Inflammation Research, 2008)

Rat cardiac mast cell maturation and differentiation following acute ventricular volume overload - M. F. Forman; G. L. Brower; J. S. Janicki (Inflammation Research, 2006)

Spontaneous histamine secretion during isolation of rat cardiac mast cells - M. F. Forman; G. L. Brower; J. S. Janicki (Inflammation Research, 2004)

The persistence of infectivity of Tetracapsula bryosalmonae ‐infected water for rainbow trout, Oncorhynchus mykiss (Walbaum) - P De Kinkelin; M Gay; S Forman (Journal of Fish Diseases, 2002)
Proliferative kidney disease (PKD) is caused by the infection of susceptible salmonid fish with spores of the myxozoan Tetracapsula bryosalmonae , a parasite harboured and released by several species of bryozoans. Under natural conditions, PKD is a water‐borne infection of fish, whose outcome and spatio‐temporal dissemination depend on the viability of spores present in the water. In order to evaluate the duration of parasite infectivity, juvenile rainbow trout, Oncorhynchus mykiss , were exposed for 20 h to T. bryosalmonae ‐infected water at various times post‐water collection or after different filtration procedures. When infected water was held in a temperature range of 14.5–17 °C for up to 14 days, PKD was transmitted to the fish only between 0 and 12 h post‐water collection and its infectivity vanished between 12 and 24 h. Similarly, the infectivity of water passed through 25 μm but not through 1 μm mesh filters, and was lost in the material eluted from the 1 μm filtration membrane although the parasite's DNA was amplified from this material. The parasitic infectivity in water appears to be fragile and this may offer opportunities to decrease the impact of PKD in trout farms by the implementation of management procedures aimed at reducing the number of the bryozoan‐holding surfaces located in the river, immediately upstream from these farms.

Monitoring the changing pattern of esophago-gastric cancer: data from a UK regional cancer registry - John Wayman; David Forman; S. Michael Griffin (Cancer Causes & Control, 2001)

Serum tocopherols, selenium and lung cancer risk among tin miners in China - Duminda Ratnasinghe; Joseph A. Tangrea; Michele R. Forman; Terry Hartman; Elaine W. Gunter; You-Lin Qiao; Shu-Xiang Yao; Michael J. Barett; Carol A. Giffen; Yener Erozan; Melvyn S. Tockman; Philip R. Taylor (Cancer Causes & Control, 2000)